Analisis Keterampilan Berpikir Kritis Kimia Siswa Kelas XI Berdasarkan Pelaksanaan Kurikulum Merdeka Belajar - Ananditha, Chintya; Andayani, Yayuk; Muntari, Muntari (FKIP University of Mataram, 2024)
Critical thinking skills are very necessary in solving problems in chemistry in the form of theories, concepts, laws and facts. Chemistry lessons not only develop knowledge, understanding and analytical skills but also need to develop students' critical thinking abilities. The aim of this research is to describe the chemistry critical thinking skills of class XI students at SMA Negeri 1 Gunungsari based on the implementation of the independent learning curriculum. This research is quantitative research using descriptive methods. The research results show that the students' critical thinking skills scores are in the high category with a percentage of 80.2%. Dominantly, the critical thinking skills obtained by class XI IPA A students are in the sufficient category with a percentage of 77.9% and the critical thinking skills obtained by class XI IPA B students are in the very high category with a percentage of 82.1%. Likewise, the percentage value of critical thinking skills indicators obtained by class XI IPA A students is lower than class XI IPA B students but is still in the high category.